(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Delayed recovery from anesthesia is one of the important challenges that face anesthesiologist. The time of delayed recovery from anesthesia is related to anesthetic agent, patient, duration and type of surgery. Objective: To determine the factors from the patients and other things related to delayed recovery after giving anesthesia. Methods: A total of 286 patients were observed in Shar Medical Hospital and Cardiac Center in Sulaimani city, Iraq between November 2019 and March 2020. Post-operative evaluation and observation were collected for delayed and normal recovery after anesthesia. P value less than 0.05 means significant relationship were obtained between variables. Results: From the 286 patients, 180 (62.94%) were male, in which 66 of them were have delayed recovery and significant relation was found p=0.005. Most of the patients were >50 years-old 126 (44.05%) and there was significant relation between age and delayed recovery of consciousness p=0.01. Delayed recovery was found among overweight more frequently than the underweight and normal weight (51 from 73 for overweight, 33 from 45 and 7 from 168, respectively). Also, significant relationship was found p=0.001. Conclusion: Old age, male, obese patients and cigarette smokers, diabetes mellitus, cerebrovascular accident, history of myocardial infarction, hyperlipidemia, and neurological diseases are high risk factors for delayed recovery. Keywords: Anesthesia, delayed recovery, post-operative care, risk factors Citation: Karim SB. Factors related to delayed recovery after anesthesia. Iraqi JMS. 2021; 19(1): 39-48. doi: 10.22578/IJMS.19.1.6